The wrapping and storage effect at zero degree during the persimmon fruit cv. Taubaté ripening - Moura, Marcelo Amaral de; Lopes, Luiz Carlos; Cardoso, Antônio Américo; Miranda, Luiz Carlos Guedes de (Pesquisa Agropecuaria Brasileira, 1997)
The experiment was undertaken in order to evaluate physical and chemical changes on persimmon (Diospyros kaki L.) fruits, cv. Taubaté, stored at 0oC, wrapped or not with PVC plastic film. Fruits were harvested at 1992 season at the Experimental Station of Araponga, MG, Brazil, and transported to the postharvest laboratory at the UFV campus, where they were selected. Fruits were disposed on 144 synthetic trays, with four fruits each. Half of the trays were wrapped with PVC. Fruits were sampled each four days. The experimental design was totally randomized and the results were submitted to statistical analysis, using test F, with 1% and 5% of significance. The storage at 0oC was efficient on slowing fruit ripening (during a 72-day period), mainly when the fruits were wrapped. After the storage at 0oC for 72 days, ripening must be induced in order to obtain a homogeneous maturation. Wrapped fruits at the end of the storage period showed a higher total chlorophyll content, reduced weight loss, and soluble solids.